Fashion in the context of social history and teaching (Research, Society and Development, 2020)
The history of fashion reveals a lot about society and its time. This article aimed to describe fashion in the context of social history and to highlight the teaching and construction of fashion knowledge. The methodology is characterized as qualitative of a descriptive nature and also as historical-evolutionary. From this framework, it was possible to infer that, starting with the Industrial Revolution, there was also a need for professionalization of fashion and teaching in fashion courses had to provide the relationship between theory and practice, to develop essential skills for the production of fashion clothing, addressed within the scope of formal training and, at the same time, meeting market demands and also the individualities present in the individual of postmodern society.